2014
DOI: 10.5114/cipp.2014.43096
|View full text |Cite
|
Sign up to set email alerts
|

Sense of coherence: big five correlates, spirituality, and incremental validity

Abstract: background Antonovsky (1987) developed the Sense of Coherence (SOC) scale to measure the "life orientation" that promotes an individual's ability to recognize life stressors and then effectively utilize coping resources to adjust and maintain health. Although theoretically appealing, little empirical work has been conducted to isolate the qualities of the scale that facilitate health. participants and procedureThe present study examined the factor structure of the SOC scale, as well as its incremental validity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
1
3
0
1
Order By: Relevance
“…This is in line with research showing that having a feeling of purpose in life can help people overcome mental health issues (Kashdan and McKnight 2013). Piedmont and colleagues found that SOC's predictive validity for various outcomes including life satisfaction, wellbeing, and affect was attenuated after accounting for meaning in life (Piedmont et al 2014). The first item of the SOC-13 scale, which is also part of the meaningfulness factor, reads "Do you have the feeling that you don't really care about what goes on around you?".…”
Section: ; Gignacsupporting
confidence: 82%
“…This is in line with research showing that having a feeling of purpose in life can help people overcome mental health issues (Kashdan and McKnight 2013). Piedmont and colleagues found that SOC's predictive validity for various outcomes including life satisfaction, wellbeing, and affect was attenuated after accounting for meaning in life (Piedmont et al 2014). The first item of the SOC-13 scale, which is also part of the meaningfulness factor, reads "Do you have the feeling that you don't really care about what goes on around you?".…”
Section: ; Gignacsupporting
confidence: 82%
“…Recent research has demonstrated that SOC possesses a large variance overlap with measures of meaning in life. Piedmont, Magyar-Russell, DiLella, and Matter (2014) found that once they controlled for meaning in life as well as self-actualization, SOC's predictive validity for various outcomes including life satisfaction, well-being, and affect was attenuated. Our own results mirror the importance of meaning as we compared different factor models of the SOC scale with regard to their criterion validity.…”
Section: Discussionmentioning
confidence: 99%
“…Antonovsky attested religion an important role as a macrosocial generalized resistance resource [43], but he did not incorporate items dealing with transcendent aspects in his SOC questionnaire [44]. In accordance with this finding, Piedmont and colleagues [45] conclude that "SOC appears more oriented towards a secular-type of meaning-making" (p. 7). This interpretation is backed up by factor analyses showing that R/S and SOC items load on different factors [46].…”
Section: Conceptualizing and Measuring Sense Of Coherencementioning
confidence: 99%